Republic of Mozambique Agriculture Public Expenditure Review : Assessment and Result-Focused Expenditure Management - World Bank Group (World Bank, Washington, DC, 2019)
The structure of the report reflects the sequence of topics which comprise the theory of change (ToC) and supporting results framework (RF) with respect to achieving sustainable results from prioritized agricultural public expenditures. Chapter 1 outlines the main macro and sectoral challenges which underpins the rationale for carrying out the agriculture public expenditure review (PER). Chapter 2 outlines the methodological aspects, key sectoral policies/strategies/targets; analyses of agricultural expenditure levels/trends, composition, relevant measures of efficiency, effectiveness and value of money; and criteria for defining the scope of the study. Chapter 3 outlines the Government’s budgetary cycle, processes and practices based on relevant budgetary decrees/circulars that guide budgetary priorities and allocations for annual and medium-term agricultural sector expenditure, and management aspects. Chapter 4 conducts a backward assessment through an analyses of the levels, trends, composition, and performance of agricultural including the efficiency, effectiveness and emerging results of agricultural public expenditure, for the period 2013 – 2017. Chapter 5 synthesizes the expenditure performance of three strategic programs: agricultural technology, irrigation, and aspects related to decentralization and adaptation to climate change. Chapter 6 highlights the role, scope, levels/trends and sources of private sector financing in the agricultural sector, and their key determinants. Chapter 7 takes a forward-looking approach to the expenditure assessment by outlining: (a) key elements and emerging issues; (b) the approach used for estimating and using their medium-term expenditure framework; (c) good practices; and (d) alignment between the forward sectoral expenditure and priority agricultural sector policies and targets. Chapter 8 synthesizes the main findings and priority recommendations in the form of a roadmap, including a supporting proposed results-focused agriculture expenditure action plan.